DIDACTIC CONDITIONS FOR THE PREPARATION OF STUDENTS OF VOCATIONAL EDUCATION FOR PROFESSIONAL ACTIVITY BASED ON AN INNOVATIVE APPROACH (Academia Science Repository, 2023)
This article discusses pedagogical conditions-the conditions of the environment in which pedagogical factors arise. The requirement of pedagogical conditions can be considered as a set of measures to ensure the achievement of a professional and creative level of thinking in the learning process. Today, the problem of the formation of a free personality requires the transfer of educational work in educational institutions to modern pedagogical technologies.